Medical Boards and CEOs - Jin, Dunhong; Lu, Fangzhou; Li, Sixuan; Yan, Chao (The Review of Corporate Finance Studies, 2026)
About 37% of Chinese listed firms have medical expertise, as measured by the existence of senior executives with a medical degree or medical-industry experience. Using the COVID-19 outbreak in China as a natural experiment, we find that the stock returns of firms with medical expertise, excluding those within the healthcare and pharmaceutical industry, are significantly higher than those without. The positive impact is more pronounced if a CEO or Chairman has medical expertise and if the firm is not state-owned. Overall, this study underlines the importance of diversified executive human capital on firm performance through disentangling macro shocks.